Розробка методики "оцінка відповідності" в рамках системи управління якості на фармацевтичному підприємстві - Коваленко, Світлана Миколаївна; Літвінова, Олена Вячеславівна; Ткаченко, Олена Валентинівна; Дядюн, Тетяна Валеріївна (Національний технічний університет "Харківський політехнічний інститут", 2021)
Метою роботи є формування методики «Оцінка відповідності» в рамках впровадження систем екологічного та енергетичного менеджменту в умовах формування інтегрованої системи управління на фармацевтичному підприємстві. Розроблено методику «Оцінка відповідності» та Лист оцінювання відповідності законодавчим та іншим вимогам у сфері екологічного менеджменту та енергоменеджменту для забезпечення можливості розглядати процеси інтегрованої системи якості з позицій їх впливу на відповідність результатів діяльності підприємства встановленим вимогам зацікавлених сторін, раціональне використання енергетичних ресурсів, визначати екологічні аспекти та їх впливи на навколишнє середовище, планувати та реалізовувати заходи управління для мінімізації ризиків, а також сприяти реалізації можливостей шляхом визначення пріоритетів діяльності фармацевтичного підприємства.

The aim of the work is to form a mandatory methodology "Conformity Assessment" within the framework of the implementation of environmental and energy management systems in the context of the formation of an integrated management system at a pharmaceutical enterprise. It has been proven that the creation of an integrated quality system at a pharmaceutical enterprise will optimize all types of resources, combine and interconnect management processes, reduce possible contradictions between various aspects of an organization's activities, reduce the cost of developing, operating and certifying an enterprise management system, create a unified training system and a management system. documentation. The "Conformity Assessment" methodology and the Conformity Assessment Sheet to legislative and other requirements in the field of environmental management and energy management have been developed to provide an opportunity to consider the processes of the integrated quality system from the standpoint of their impact on the compliance of the enterprise's performance with the established requirements of stakeholders, rational use of energy resources, determine environmental aspects and their impact on the environment, plan and implement management measures to minimize risks, and contribute to the realization of opportunities by prioritizing the activities of the pharmaceutical enterprise.
Development of the ''conformity assessment'' methodology within the quality management system at a pharmaceutical enterprise
Keywords: інтегрована система якості; екологічний менеджмент; енергоменеджмент; оцінка відповідності; фармацевтичні підприємства; integrated quality system; environmental management; energy management; conformiy assessment